2020
DOI: 10.5194/gmd-2020-152
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Testing the Reliability of Interpretable Neural Networks in Geoscience Using the Madden-Julian Oscillation

Abstract: Abstract. We test the reliability of two neural network interpretation techniques, backward optimization and layerwise relevance propagation, within geoscientific applications by applying them to a commonly studied geophysical phenomenon, the Madden-Julian Oscillation. The Madden-Julian Oscillation is a multi-scale pattern within the tropical atmosphere that has been extensively studied over the past decades, which makes it an ideal test case to ensure the interpretability methods can recover the current state… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…At lead 0, where the classification model is identifying the MJO, the phase of active MJO events are correctly predicted with an accuracy of ∼80% (Figure 6), comparable to Toms et al. (2019), despite differences in our input variables, data pre‐processing, MJO index, and ANN complexity. The majority of incorrectly predicted active MJO events at short leads are near the boundary between two RMM phases and predictions are often incorrect by only one phase.…”
Section: Resultssupporting
confidence: 79%
“…At lead 0, where the classification model is identifying the MJO, the phase of active MJO events are correctly predicted with an accuracy of ∼80% (Figure 6), comparable to Toms et al. (2019), despite differences in our input variables, data pre‐processing, MJO index, and ANN complexity. The majority of incorrectly predicted active MJO events at short leads are near the boundary between two RMM phases and predictions are often incorrect by only one phase.…”
Section: Resultssupporting
confidence: 79%
“…Gagne et al [81] used feature importance and feature optimization to interpret their CNN model for predicting the probability of severe hailstorms and found that the model synthesized information about the environment and storm morphology that is consistent with our current understanding of the physics of hailstorms. Toms et al [82] developed interpretable NNs for the geosciences and showed their usefulness and reliability in improving our understanding of the Madden-Julian oscillation [83]. Brenowitz et al [43] developed an interpretability framework specialized for analysis of the relationship between offline skill versus online coupled prognostic performance for ML parameterizations of convection.…”
Section: Physics-informed Machine Learning: Objectives Approaches Applicationsmentioning
confidence: 99%
“…Our usage of LRP, therefore, offers insights into which patterns of SST variability lend predictability of decadal surface temperature anomalies over continental North America within CESM2. A more detailed discussion of LRP and its applicability to Earth-system research is discussed in Toms, Barnes, and Ebert-Uphoff (2020), and additional applications are available in Barnes et al (2020), Ebert-Uphoff and Hilburn (2020), and Toms, Kashinath, et al (2020).…”
Section: Toms Et Almentioning
confidence: 99%
“…The specific usage of neural network interpretation techniques ranges substantially across such studies, however, the interpretations can be used as either direct or indirect tools for scientific discovery. For example, interpretation efforts can be either a secondary objective by ensuring a network's reasoning is consistent with existing physical theory (e.g., Brenowitz et al, 2020;Ebert-Uphoff and Hilburn, 2020;Toms, Kashinath, et al, 2020), or the primary objective, with their usage focused on discovering new patterns of Earth-system variability (e.g., Barnes et al, 2020;. Here, we focus on the latter application, whereby we use neural networks to identify predictable modes of Earth-system variability on decadal timescales in a fully coupled Earth-system model.An extensive body of literature exists on theoretical and observed sources of decadal predictability, and more recently, on the development of operational decadal prediction systems (Yeager et al, 2018).…”
mentioning
confidence: 99%